Harnessing the bone-seeking ability of Ca(ii)-like metal ions in the treatment of metastatic cancer and resorption disorders. (8th February 2016) - Weekes, D. M.; Orvig, C.
Abstract : In this tutorial review, we explore how a special relationship between metal ions and bones has been exploited to target therapeutic agents. Abstract : Metal ions are naturally retained by skeletal tissues in living systems because of their high affinity for the hydroxyapatite-like mineral matrix that makes up cortical bone. This is particularly true for metal ions that bear a close resemblance to calcium(ii ) (such as the lanthanides or alkaline earth metals), and in a few key cases this targeting ability has been exploited in order to develop medicinal agents that are intended to treat bones which have become diseased. In this review, we focus on two areas where this has been particularly effective: first is in the diagnosis and therapy of metastatic bone cancer, in which radioactive metal ions including 99m Tc, 153 Sm, and 223 Ra are used to image, alleviate, and ablate harmful cancerous legions with good specificity versus healthy tissues; second is the use of trivalent lanthanides to treat osteoporosis, an emerging concept which has gathered significance over the last 15 years, and is now entering preclinical trials with carefully designed systems.